Intercultural communication globalization and social justice - Sorrells, Kathryn (SAGE, 2022)
Intercultural Communication: Globalization and Social Justice, Third Edition, introduces students to the study of communication among cultures within the broader context of globalization. Kathryn Sorrells highlights history, power, and global institutions as central to understanding the relationships and contexts that shape intercultural communication. Based on a framework that promotes critical thinking, reflection, and action, this text takes a social justice approach that provides students with the skills and knowledge to create a more equitable world through communication"--